Store-Related Injuries to Children and Adults. (September 2015) - Kim, Robyn; Crump, Caroline; Harley, Erin; Nauhaus, Genevieve; Yigit-Elliott, Serap
The present study investigated in detail the circumstances and patterns of injury experienced by adults and children in retail store environments in the United States. Data from the CPSC's National Electronic Injury Surveillance System (NEISS) database were analyzed, yielding a total national estimate of 85, 403 injuries occurring inside stores for the year 2012. Injuries were analyzed by severity, type of injury, accident mode, objects/conditions involved in the accident, and age of the injured. The majority of store-related injuries were not severe, and did not involve interaction with store-related objects or factors unique to store environments. The most common accident modes were general falls, unintentional contact with an object or person, falls from objects (such as carts) and slips. Children under the age of 5 had the highest rates of injury, most commonly resulting from falls from shopping carts. Adults over the age of 65 had the second highest rates of injury, typically resulting from general falls not caused by specific store-related objects.